Decision Support System for Rural Health Units with Mapping - Dr. Mukesh Mishra (International Journal of Engineering and Management Research, 2022)
The amount of data and technology available in this demanding and difficult world is overwhelming. However, certain organizations—like the Rural Health Unit of the Municipality of Solano, Nueva Vizcaya—continue to conduct their business manually as of right now. The unit's problems, issues, and obstacles in providing medical services were highlighted, along with the degree of conformity with ISO/IEC 25010 Software Quality Standards. Additionally, illnesses can be managed and treated utilizing data mining techniques to forecast the occurrence of diseases due to the unpredictable availability of data. The present investigation employed clustering and classification data mining techniques to forecast the incidence of disease in each barangay within the municipality within a specific timeframe. To address the unit's issues, a decision support system and an effective record management system were created. Its primary feature is the disease-occurrence mapping, which helps the unit's doctors and other medical professionals make decisions about diagnosis, treatment, and recommendations. According to the ISO/IEC 25010 Software Quality Standards, the system received a qualitative rating of "very great extent."